2009
DOI: 10.1148/radiol.2533071654
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Glioblastoma Multiforme: IncreasedMyo-inositol and Glutamine Levels in the Contralateral Cerebral Hemisphere at Proton MR Spectroscopy

Abstract: Increased concentrations of myo-inositol and glutamine in the contralateral normal-appearing white matter of GBM patients are consistent with mild astrocytosis and suggest the detectability of early neoplastic infiltration by using proton MR spectroscopy in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 34 publications
2
59
3
1
Order By: Relevance
“…The results in this study may, to some extent, also be attributed to diaschisis, which refers to metabolic and functional changes remote from the origin but communicating with the damaged focus via anatomical structures [36]. However, previous MRS findings in normal appearing white matter in tumor patients indicate the presence of proliferative processes [18].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The results in this study may, to some extent, also be attributed to diaschisis, which refers to metabolic and functional changes remote from the origin but communicating with the damaged focus via anatomical structures [36]. However, previous MRS findings in normal appearing white matter in tumor patients indicate the presence of proliferative processes [18].…”
Section: Discussionmentioning
confidence: 77%
“…Several studies have reported the infiltrative growth of glioblastoma multiforme (GBM) cells in apparently unaffected brain regions remote from the confirmed primary lesion [5,17,24,32] without correlating changes on computed tomographic or MR images [20,38]. Diffusion tensor imaging (DTI) [2,14,34] and localized proton MRS provided subtle hints towards remote infiltration of GBM cells [4,14,18]. This work investigated the use of DTI and corresponding metrics as putative indicators of the invasiveness of malignant brain tumors.…”
Section: Communicating Authormentioning
confidence: 99%
“…We found that the CSF myo-inositol levels decrease, whereas cholesteryl sulfate level increases linearly respect to tumor size as measured by Tgad and FLAIR according to the Macdonald's criteria. Myo-inositol is a cerebral osmolyte found to be significantly lowered in glioblastomas and anaplastic astrocytomas than in low-grade gliomas and normal brain tissue as detected by magnetic resonance spectroscopy (MRS) (46,47). Consistent with the previous MRS findings that decreasing myo-inositol level was associated with increasing aggressiveness of the glioma phenotype, our data also showed that the tumor size in our cohort negatively correlated with myo-inositol levels in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown that the spectroscopic abnormality is 20% larger than the volume of increased T 2 signal and biopsies of this region show evidence of tumour invasion [67]. Other studies have detected increases in myoinositol (a spectroscopic marker of glia) and glutamate (implicated with anabolic pathways upregulated in tumours) in the contralateral hemisphere of glioblastomas [68]. This change was not seen in either low-grade gliomas or normal controls.…”
Section: Tumour Metabolismmentioning
confidence: 98%